Port of Spain, Trinidad - (:unkn) unknown (My University, 2011)
A picture of Port of Spain. In this picture you can see a boat as it approaches the harbour. You can see the hills of the Northern Range and buildings. At far right are the customhouses and the lighthouse.
Colour: Sepia; Style: Landscape; Other: Unbordered and Undivided.
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Harbors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1920]; Paria, Gulf of (Venezuela and Trinidad and Tobago); Buildings--Trinidad and Tobago; Mountains--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Lighthouses--Trinidad and Tobago; Storage tanks--Trinidad and Tobago